FOREIGN POLICY OF THE REPUBLIC OF KOREA: THE ORGANIZATIONAL AND LEGAL FRAMEWORK (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the institutional and legal foundations of the foreign policy activities of the Republic of Korea. The study highlights the role and significance of the key normative legal documents that shape the country’s foreign policy, including the Constitution, the National Security Strategy, and the Defense White Paper. In addition, the functional role of the Ministry of Foreign Affairs of the Republic of Korea is examined. The article also analyzes the main principles of foreign policy and their legal basis, revealing the mechanisms of their practical application. Furthermore, the specific features of the foreign policy of the Republic of Korea are compared with those of other countries’ foreign policy approaches.
Keywords: foreign policy, Republic of Korea, National Security Strategy, Defense White Paper, Ministry of Foreign Affairs, state protocol, middle power diplomacy, institutional framework.